1998
DOI: 10.1038/sj.gt.3300764
|View full text |Cite
|
Sign up to set email alerts
|

Gene transfer of tissue inhibitor of metalloproteinase-2 inhibits metalloproteinase activity and neointima formation in human saphenous veins

Abstract: Metalloproteinases (MMPs) are implicated in neointima for-21.8 ± 2.9 ng/mg wet weight/day (P Ͻ 0.05, n = 3). In situ mation and hence vein graft failure. Gene transfer to elevzymography revealed a marked inhibition of gelatinolytic ate local levels of tissue inhibitor of metalloproteinases activity by TIMP-2 gene transfer throughout the vein seg-(TIMPs) is therefore a potential treatment. In this study, we ments. Neointima formation and neointimal cell numbers have used lumenal application of a replication-def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
86
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(90 citation statements)
references
References 34 publications
3
86
0
1
Order By: Relevance
“…George and colleagues reported that TIMP-2 overexpression using an adenovirus reduces neointimal thickening, primarily by inhibiting MMP activity and blocking SMC migration (33). This group later showed that adenovirus-mediated TIMP-3 overexpression inhibits late vein graft neointima formation in human and porcine models (34).…”
Section: Discussionmentioning
confidence: 90%
“…George and colleagues reported that TIMP-2 overexpression using an adenovirus reduces neointimal thickening, primarily by inhibiting MMP activity and blocking SMC migration (33). This group later showed that adenovirus-mediated TIMP-3 overexpression inhibits late vein graft neointima formation in human and porcine models (34).…”
Section: Discussionmentioning
confidence: 90%
“…11 Our previous studies in human and pig models of vein graft neointimal thickening have highlighted the potential benefit of matrix metalloproteinase (MMP) inhibition in prevention of vein graft neointimal hyperplasia. 8,9,13,15 In particular, we demonstrated that inhibition of SMC migration by MMP combined with induction of SMC apoptosis by TIMP-3 overexpression was beneficial in human and pig models. 13 Other pro-death strategies have demonstrated efficacy in post-angioplasty restenosis models by overexpression of thymidine kinase.…”
Section: Introductionmentioning
confidence: 83%
“…Gene Therapy (2001) 8, 668-676. potential therapies. 6 To date, a number of studies have targeted different mechanisms involved in the progression of vein graft neointimal thickening, [7][8][9][10][11][12][13] and recently, clinical trials have been initiated. 14 Mann et al 10,11 modulated the cell cycle using antisense oligonucleotides targeting proliferating cell nuclear antigen (PCNA) or cell division cycle 2 (cdc 2) kinase, and reduced neointimal hyperplasia 10 through enhanced nitric oxide bioavailabilty and reduced monocyte adhesion and vascular cell adhesion molecule-1 (VCAM-1) expression.…”
Section: Introductionmentioning
confidence: 99%
“…In evaluating the EC-specific activity of the FLT-1 promoter in human saphenous vein, we demonstrated potential clinical utility for FLT-1 when delivered locally into human vessels for delivery of therapeutic genes, such as metalloproteinase inhibitors. 17,21 Furthermore, it is clear that systemic dissemination of virus may have deleterious consequences, particularly for prodeath or proangiogenic genes. [22][23][24][25][26] We found that FLT-1 activity in hepatocytes in vitro and in vivo was extremely low, which indicates that if vector dissemination occurred during local delivery to the vessel wall, the use of FLT-1 would avoid undesirable transgene expression in the liver.…”
Section: Discussionmentioning
confidence: 99%